Development of a Novel, Fast, Simple HPLC Method for Determination of Atorvastatin and its Impurities in Tablets - Shulyak, N.; Piponski, M.; Kovalenko, S.; Stoimenova, T. B.; Balkanov, T.; El-Subbagh, H.I.; Drapak, I.; Omotosho, J.O.; Logoyda, L.; Коваленко, Сергій Іванович (My University, 2021)
Our main target and concept was to develop a method for the determination of the most prescribed antilipemic drug, atorvastatin, together with its related substances, with a single sample preparation and during a single chromatographic run, in the shortest possible period of time, with the lowest possible mobile phase consumption. A new rapid, simple chromatographic method for the determination of atorvastatin and its main specified impurities was developed, using different chromatographic columns. With this new concept of a mobile phase and a powerful core–shell, or a superficially porous silica-based column, satisfactory results for targeted parameters, such as critical peak resolution, run time length, and column backpressure, were achieved. The analysis is performed within a run duration of less than 15 minutes, which is about six times shorter than the official European Pharmacopoeia method. The chromatogram performances suggests that the method limit of quantification (LOQ) can be about 7 times lower, and the limit of detection (LOD) about 20 times lower, using an injection volume of only 2 μl. This was confirmed by the performed method validation in accordance with the International Conference on Harmonization (ICH) guideline for the validation of analytical procedures Q2(R1), where the selectivity, linearity, accuracy, precision, limit of quantification, and limit of detection were tested and confirmed.
Keywords: atorvastatin; impurities; liquid chromatography; method optimization; tablets